2020
DOI: 10.2147/cmar.s250792
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identification and Validation of Novel Genes in Anaplastic Thyroid Carcinoma via Bioinformatics Analysis</p>

Abstract: The conventional interventions of anaplastic thyroid carcinoma (ATC) patients are mainly through surgery, chemotherapy, and radiotherapy; however, it is hardly to improve survival rate. We aimed to investigate the differential expressed genes (DEGs) between ATC and normal thyroid gland through bioinformatics analysis of the microarray datasets and find new potential therapeutic targets for ATC. Methods: Microarray datasets GSE9115, GSE29265, GSE33630, GSE53072, and GSE65144 were downloaded from Gene Expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…CENPF is already known as thyroid carcinoma biomarker, involved in migration and proliferation[ 61 ]. Interestingly, anaplastic TC, the most aggressive histological TC is enriched in genes involved in the mitosis progression including CENPF , NEK2 and NUSAP1 [ 62 , 63 ] . We also identified several aging-dependent TFs that are upregulated in TCs, such as FOXM1 and SOX11, both of which have fundamental roles in tumorigenesis and aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…CENPF is already known as thyroid carcinoma biomarker, involved in migration and proliferation[ 61 ]. Interestingly, anaplastic TC, the most aggressive histological TC is enriched in genes involved in the mitosis progression including CENPF , NEK2 and NUSAP1 [ 62 , 63 ] . We also identified several aging-dependent TFs that are upregulated in TCs, such as FOXM1 and SOX11, both of which have fundamental roles in tumorigenesis and aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Although it accounts for only 2% of all THCA, ATC has a high mortality rate and was the main cause of THCA death (2). Moreover, epidemiological surveys showed that the incidence of ATC increased from 1973 to 2014 (12). Therefore, it is clinically significant to explore effective treatment methods to improve the prognosis of ATC patients.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained ATC gene expression profiling datasets (11,12), GSE65144 GSE33630, GSE29265 (no citation), and GSE53157, from the GEO (https://www.ncbi.nlm.nih. gov/geo/) database.…”
Section: Transcriptome Data Acquisition and Pre-processingmentioning
confidence: 99%
“…The DEMGs were then subjected to functional enrichment and protein-protein interaction (PPI) analyses. PPI analysis was set with an interaction score of 0.4 [19,20] and exclusion of hidden disconnected nodes. The interaction data were imported into Cytoscape to find hub genes based on Degree, Maximum Neighborhood component (MNC), Closeness, and Maximal Clique Centrality (MCC) algorithms.…”
Section: Plos Onementioning
confidence: 99%